Numerical Simulation of a Radiant Floor Cooling Office Based on CFD-BES Coupling and FEM. (May 2017) - Kong, Qiongxiang; Feng, Ji; Yang, Chunlei; Miao, Zhen; He, Xiao
Abstract: In this paper, in order to accurately simulate building thermal performance, a coupling strategy between the hourly Computational Fluid Dynamics (CFD) simulation of the indoor airflow in a room and the dynamic Building Energy Simulation (BES) of the heat transfer through its envelope based on real-time information exchange is developed, and the radiation heat transfer among the internal surfaces of its envelope is also calculated. The governing equations are solved by Finite Element Method (FEM). Then, the developed program is applied to co-simulate an office room with a ventilating and radiant floor cooling system. The results show that the dynamic heat transfer characteristics of the external wall and the indoor air in the room change with outside weather conditions in detail.